Privatizing public enterprises and foreign investment in developing countries, 1988-93 - Sader, Frank (Occasional paper, 1995)
"Analyzes impact of privatization programs on direct foreign investment(DFI). Uses econometric techniques to demonstrate that infrastructure privatization is highly correlated with higher levels of subsequent DFI capital inflows"--Handbook of Latin American Studies, v. 57